1993
DOI: 10.1007/bf00159497
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of enzyme activities in the brain

Abstract: The present review focuses on enzymes involved in the metabolism of amino acid neurotransmitters and the microphotometric determinations of their activities in various layers of the rat hippocampus. The enzymes are NAD-linked isocitrate dehydrogenase (NAD-ICDH), glutamate dehydrogenase (GDH), and GABA transaminase (GABAT), all of which are localized in mitochondria. GDH seems to be restricted to astrocytes, whereas NAD-ICDH and GABAT are localized in neurons as well as in astrocytes. NAD-ICDH is an important e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Indeed, oligodendroglial cells and neurons in culture can use D-,Q-hydroxybutyrate as a substrate for the generation of energy (Edmond et al, 1987) . The enzymes required for the disposal of the amino group of leucine, glutamate dehydrogenase (Kaneko et A., 1988;Kugler, 1993;Rothe et al, 1994) and glutamine synthetase (Norenberg and Martinez-Hernandez, 1979), are essentially restricted to astrocytes . Therefore, the breakdown of leucine is likely to be taking place in these cells, which forward the nitrogen-stripped metabolites to the neighboring cells as fuel material .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, oligodendroglial cells and neurons in culture can use D-,Q-hydroxybutyrate as a substrate for the generation of energy (Edmond et al, 1987) . The enzymes required for the disposal of the amino group of leucine, glutamate dehydrogenase (Kaneko et A., 1988;Kugler, 1993;Rothe et al, 1994) and glutamine synthetase (Norenberg and Martinez-Hernandez, 1979), are essentially restricted to astrocytes . Therefore, the breakdown of leucine is likely to be taking place in these cells, which forward the nitrogen-stripped metabolites to the neighboring cells as fuel material .…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is catalysed by GABA transaminase (GABA-T) which is present in mitochondria of glial cells and neurons [138140]. It is estimated that more than 90% of all GABA in the mammalian CNS is degraded in this way and contributes to energy metabolism in the tricarbonic acid cycle.…”
Section: Sequestration and Degradation Of Gabamentioning
confidence: 99%
“…Recent studies revealed that GABA transaminase has an iron-sulfur cluster at the center of the GABA transaminase dimer (Storici et al, 2004). This enzyme is synthesized in postsynaptic neurons and astrocytes (reviewed in Kugler, 1993) and plays an essential role in the degradation of GABA, which is released from GABAergic synaptic terminals. Moreover, the inherent high neural activity in the above brain regions may cause an increased turnover of ironcontaining proteins, thereby creating a high demand for iron supply.…”
Section: Topography Of Nonheme Fe(iii) and Fe(ii) Distribution In Relmentioning
confidence: 99%